DEMONSTRATE UNDERSTANDING OF COURSE-BOOKS IN THE CLASSROOM - Sultanova , Umidaxan Matkarimovna; Xaitbayeva , Sevara Kamiljanovna (GOLDEN BRAIN, 2024)
In this article, explain how explain ways a course-book could be integrated into a course curriculumю Because they give teachers and students access to helpful pre-made content, course books continue to play an important role in EFL teaching and learning. On the other hand, improper usage of course materials can wear out students and degrade teachers. This paper explores the role of course books in EFL teaching and examines how teachers can make effective use of the material. It mainly applies to novice teachers and those working in centralized systems, where decisions are made by ministries and committees. The purpose of course books, their influence on the teaching and learning processes, and the reasons for teaching course books-based, as opposed to course books-led, are discussed in the first section of the article. The article’s second section is an try to illustrate the proper utilization of course books through the application of the critical stages of assessment, selection, adaptation, and supplementing. It also directs EFL teachers to resources for direction and useful counsel.